20.2k views
2 votes
Suppose a - b =0 Which one these expressions equals ab?

Suppose a - b =0 Which one these expressions equals ab?-example-1
User Weez
by
5.4k points

1 Answer

4 votes

Okay, here we have this:

Considering the provided information we obtain that:

As a-b=0, then a=b.

And as a=b, in the expression ab, we can replace "b" and we have that: ab=aa, and finally simplifying:

aa=a².

So in summary we have:

ab

=aa

=a².

Finally we obtain that the correct answer is tha option A.

User Stevenmc
by
5.1k points